2015
DOI: 10.1002/trtr.1376
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing English Learners' Language Development Using Wordless Picture Books

Abstract: This article presents an approach to use wordless picture books to enhance the language development of English language learners. This approach is grounded in best practices to teach ELLs. The process starts with viewing and analyzing the visual images, engaging ELLs in discussion, and ending with students' self‐authored texts. The wordless picture books contain all the literary elements and text structures that books with text have. Wordless picture books, without the language demands, invite ELLs to share th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 12 publications
0
29
0
2
Order By: Relevance
“…This study was primarily influenced by previous studies demonstrating the benefits of buddy reading (e.g., Friedland & Truesdell, 2006;Kreuger & Braun, 1998;Mak et al, 2008) and reading picture books (e.g., Louie & Sierschynski, 2015;Sheu, 2008;Sun, 2015). To begin with, buddy reading is a reading approach that involves students reading books to a partner who may be younger or at a lower reading proficiency level (e.g., Mak et al, 2008;Shegar, 2009;Theurer & Schmidt, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was primarily influenced by previous studies demonstrating the benefits of buddy reading (e.g., Friedland & Truesdell, 2006;Kreuger & Braun, 1998;Mak et al, 2008) and reading picture books (e.g., Louie & Sierschynski, 2015;Sheu, 2008;Sun, 2015). To begin with, buddy reading is a reading approach that involves students reading books to a partner who may be younger or at a lower reading proficiency level (e.g., Mak et al, 2008;Shegar, 2009;Theurer & Schmidt, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In L2 education, the effects of reading picture books on L2 learning have also been evidenced in many studies. For example, research has demonstrated that reading the text and illustration components is conducive to L2 learning in several ways (e.g., Louie & Sierschynski, 2015;Sheu, 2008;Sun, 2015). In one study, Sheu (2008) found that while reading picture books students could review vocabulary and sentences and learn to use them in various settings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Children's literature markets are picking up (Bluestone, 2015) and students are starting to read books in school. Teachers are returning to children's literature as models for teaching reading and writing (Louie & Sierschynski, 2015).…”
Section: Motivation Purpose and The Return To Children's Literaturementioning
confidence: 99%
“…The story of children's literature could also motivate adult learners to learn a new language and lead them to an unknown but intriguing world of literature (Carger, 1993). English picture books, mostly suggested and often applied by language teachers, are of great help for language development and communication abilities (Freeman and Lehman, 2001; Huck, Helper, and Hickman, 1987;Louie and Sierschynski, 2015). The texts of English picture books are not as intimidating as English learning course books.…”
Section: Introductionmentioning
confidence: 99%